THE CONTINUITY OF CARE FROM PREGNANCY TO NEWBORN FOR MRS. FR AT PUBLIC HEALTH WELAHAN I JEPARA - Kusniati, Milatin; Rose Nur Hudhariani (Universitas STRADA Indonesia, 2023)
Background: The acceleration of MMR reduction is carried out by ensuring that every mother is able to access quality maternal health services, such as pregnant women's health services, childbirth. Method : Type of descriptive research case study method, place conducted at Puskesmas Welahan I. Result : Results Pregnancy care is carried out according to 10 T care standards, physiological pregnancy. The labor process applies normal labor care, proceeds normally. Conclution : The results of COC midwifery care are able to deliver mothers and babies in healthy conditions.